2021
DOI: 10.3390/ani11072137
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Dietary Supplementation with Protected Sodium Butyrate on Gut Microbiota in Growing-Finishing Pigs

Abstract: The study assessed changes in the gut microbiota of pigs after dietary supplementation with protected sodium butyrate (PSB) during the growing-fattening period (≈90 days). One gram of colon content from 18 pigs (9 from the treatment group -TG- and 9 from the control group -CG-) was collected. Bacterial DNA was extracted and 16S rRNA high-throughput amplicon sequencing used to assess microbiota changes between groups. The groups shared 75.4% of the 4697 operational taxonomic units identified. No differences in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 66 publications
5
15
0
Order By: Relevance
“…However, limited research has been conducted on the microbial mechanisms that contribute to the protective effects of butyrate on the gut. Consistent with the present study, previous research ( Bernad-Roche et al., 2021 ; Wu et al., 2018 ) showed that microbial α diversity was similar, while β diversity was different in both pigs and poultry between supplemented with or without butyrate. These results indicate a potential effect of butyrate supplementation on the structure of intestinal microbiota.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…However, limited research has been conducted on the microbial mechanisms that contribute to the protective effects of butyrate on the gut. Consistent with the present study, previous research ( Bernad-Roche et al., 2021 ; Wu et al., 2018 ) showed that microbial α diversity was similar, while β diversity was different in both pigs and poultry between supplemented with or without butyrate. These results indicate a potential effect of butyrate supplementation on the structure of intestinal microbiota.…”
Section: Discussionsupporting
confidence: 93%
“…These results indicate a potential effect of butyrate supplementation on the structure of intestinal microbiota. Like in our study, Bernad-Roche et al. (2021) and Wu et al.…”
Section: Discussionsupporting
confidence: 82%
“…As observed in the present study, Bernad-Roche et al [70] also noted a significant decrease in the relative abundance of this genus in the intestinal microbiota of growing and finishing piglets that received food supplementation with sodium butyrate. In summary, we concluded that although supplementation does not change the overall richness of the microbiota composition, it may have increased the specific taxa associated with better gut health parameters.…”
Section: Plos Onesupporting
confidence: 88%
“…The results of the linear discriminant analysis effect size (LefSe) showed that species of the family Peptostreptococcaceae were the characteristic microorganisms of the XBC microbiota (Figure 4). Peptostreptococcaceae belonging to the order Clostridiales are a group of bacteria characterized by short chain fatty acid production in the process of degradation of plant-derived cellulose and hemicellulose components (Bernad-Roche et al, 2021). Previous studies demonstrated that the abundance of the family Peptostreptococcaceae in the gut microbiota of castrated bulls was higher than in uncastrated bulls, and they exhibited distinct serum and muscle amino acid profiles, with increased muscular fat storage (Whon et al, 2021).…”
Section: Composition Of Gut Microbiotamentioning
confidence: 99%